Factors Shaping Occupational Injustice among Resettled Syrian Refugees in the United States. (20th June 2022) - Darawsheh, Wesam B.; Bewernitz, Megan; Tabbaa, Sawsan; Justiss, Michael
Abstract : Background. There have been a limited number of studies that have focused on factors which shape the experiences of resettlement and occupational injustice among refugee populations. Purpose. To explore the factors that shape the living difficulties of Syrian refugees who were lawfully admitted into the United States and ways whereby they might interfere with shaping occupational injustice. Method. Mixed methodologies were incorporated. The living difficulty scale for refugees (LDSR) was disseminated. Semistructured interviews were conducted, and fieldnotes were collected as sources of qualitative data. Results. 254 participants (mean age 36.2 ± 9.6 yrs; 159 females and 95 males) completed the survey, and nine of them participated in the semistructured interviews. Age (p < 0.01 ), region (p < 0.001 ), and time in the United States (p < 0.05 ) had significant effects on the experiences of the participants, but not gender (p = 0.308 ). Occupational injustice is an outcome of an interaction between interpersonal and contextual factors. Practice Implications . Occupational therapists need to assume a vital role in maximizing opportunities of engagement in meaningful occupations for Syrian refugees to counteract occupational injustice and difficulties associated with resettlement.